Investigation on enzymatic activity of rubber seed as source of plant lipase / Noor Fatiha Ahmad Bahrin, Harumi Veny, and Siti Zainab Che Mat - Ahmad Bahrin, Noor Fatiha; Veny, Harumi; Che Mat, Siti Zainab (Universiti Teknologi MARA Shah Alam, 2020)
Rubber seed is a non-edible seed that is abundantly available and considers agricultural wastes. A potential lipase from rubber seed was examined based on the enzymatic activity and its application in the hydrolysis reaction. The enzymatic activity characterization study was determined based on p-nitrophenol release in the hydrolysis reaction. The initial evaluation showed that temperature and pH significantly influence the reaction. The optimum condition based on enzymatic activity for rubber seed was found at 30 ℃ and pH 8. The rubber seed lipase extract was then used in enzymatic hydrolysis reactions of rubber seed oil, palm oil, and canola oil. The highest FFA percentage of 63% was found from the rubber seed oil. The results indicate that rubber seed extract has shown its potential enzymatic activity. However, further studies need to be done to apply this rubber seed in various lipase catalysed reactions.